Dinamika Sektor Pariwisata sebagai Katalisator Pertumbuhan Ekonomi Indonesia: Kajian Literatur Sistematis - Wahyu Muh. Syata (Edupreneurship: Jurnal Pendidikan Ekonomi, 2026)
This study aims to comprehensively analyze the role of the tourism sector in driving Indonesia's economic growth through a literature review. The research method employed is library research with a qualitative descriptive approach, utilizing content analysis and literature synthesis relevant scientific journal articles. The results indicate that the tourism sector has a positive and significant contribution to Indonesia's economic growth through various channels, including increased foreign exchange earnings, multiplier effects on supporting sectors such as transportation, hospitality, and trade, job creation, increased local revenue, and encouraging investment in infrastructure and accommodation sectors. Other important findings reveal that digital transformation, synergy with the creative economy, halal tourism development, and strategic policies such as visa-free visits also strengthen the tourism sector's contribution to the national economy. Domestic tourists also play a crucial role in maintaining the stability of the tourism sector, especially during global crises. This study recommends strengthening cross-sector coordination, increasing infrastructure investment, developing human resources, accelerating digital transformation, and formulating regulations that support sustainable and inclusive tourism. In conclusion, the tourism sector has proven to be a multifaceted catalyst for Indonesia's economic growth, yet its effectiveness is highly dependent on the specific conditions of each region and integrated policy support